PWE-008 Dosing, durability of haemoglobin response and safety of iron isomaltoside in patients with gastrointestinal diseases. (June 2019) - Thomas, Amanda; Cairnes, Vida; Mole, Sean; Elworthy, Claire; Figueredo, Juan Saucedo; Goodhand, James R; Ahmad, Tariq; Kennedy, Nicholas A
Abstract : Introduction: Iron deficiency anaemia (IDA) commonly complicates gastrointestinal disease and impairs quality of life (QoL). Intravenous iron therapy is widely used in IDA when oral iron is poorly tolerated or ineffective, and normalisation of haemoglobin improves QoL scores. We sought to define the dosing regimens of, durability of haemoglobin responses and the prevalence of adverse events to intravenous iron (III) isomaltoside (Monofer). Methods: We undertook a service evaluation of intravenous iron use in 508 outpatients (40% male) with gastrointestinal disease treated with 648 Monofer infusions between 2014 and 2017. Demographic, diagnosis, and treatment factors including dose of Monofer used and the number of patients treated with repeat infusions were recorded form the medical record. Anaemia was defined by WHO criteria. Iron deficiency was defined as transferrin saturation <18% and/or ferritin <30 µg/L (ferritin <100 µg/L if CRP >5 mg/L). We extracted laboratory results from the electronic record for baseline, 12 weeks and 52 weeks. We sought factors associated with treatment failure, defined as ongoing anaemia at 12 weeks, using logistic regression. Results: Overall, 93% (568/613) were anaemic at baseline with median (IQR) haemoglobin of 100 g/L (IQR 8–12). 73% (476/648) had haematinics tested and 91% [431/476] had proven IDA. Inflamatory bowel disease was the most common indication at 30% (193/648) infusions. A variety of dosing regimens were used: 26% (167/648) received fixed dosing of 1 g, 25% (163/648) were dosed according to the Ganzoni formula, 14% (91/648) had the dose calculated by the Ganzoni formula but limited to a single 20 mg/kg infusion, 8% (54/648) were dosed by the simplified dosing table and 27% (173/648) other dosing strategies. 74% (479/648) infusions had follow-up haemoglobin measured 6 to 18 weeks post-infusion. The median change in haemoglobin between baseline and –8 weeks was 18 g/L (IQR –9). 42% (186/438) of previously anaemic patients had normalised their haemoglobin by this time. Factors associated with failure to normalise haemoglobin were male sex (odds ratio (OR) 2.9 [95%CI 1.–.3]), age ≥65 years (OR 3.4 [95%CI 2.–.0]), higher comorbidity (OR 3.7 [95%CI 2.–.5]) and under-dosing versus Ganzoni-calculated dose (OR 4.8 per gram underdosed [95%CI 2.–0]). Only, 31% (44/143) patients whose haemoglobin normalised at week 12 had recurrent anaemia at 1 year. Adverse events were rare: only one patient had a probable complement activation-related pseudoallergy that was mitigated by slowing infusions, and there were no anaphylactic reactions. Discussion: A wide-variety of dosing strategies are used in our trust. Treatment failure was associated with under-dosing, age, sex and comorbidity. Adverse events were rare.